Epidemiological investigation of Toxoplasma gondii in Alpine red deer(Cervus elaphus) : spread and effects on pregnancy - N. Formenti; N. Ferrari; T. Trogu; P. Lanfranchi; L. Pedrotti; A. Gaffuri (Associazione Teriologica Italiana, 2014)
Several animal species can be infected by the widespread protozoan Toxoplasma gondii contributing to maintain both domestic and sylvatic parasite lifecycle and favouring the raise of public health issues related to its zoonotic value. As wild ungulates can be source of T. gondii for humans through consumption, manipulation and evisceration of carcasses, risk of infection should be evaluated in relation to the amount of game meat available from harvest plans every year. Therefore in Italy the attention should be focused on red deer (Cervus elaphus) because of the intense hunting activity in many Alpine areas and since this species is the most frequently consumed raw or undercooked. In particular, despite the well documented zoo-economic losses in livestock, little is known about the epidemiology of T. gondii infection in red deer particularly regarding any impact on populations’ dynamics. Besides no assessments are reported about T. gondii associated-reproductive pathologies in this species although vertical transmission recorded in white tailed deer (Odocoileus virginianus) and natural transplacental toxoplasmosis documented in a stillborn reindeer (Rangifer tarandus) foetus point out the hypothesis that also red deer could be affected. In addition just few studies have investigated the effect of parasitism on fecundity of ungulates in natural conditions. Here we performed a sero-epidemiological investigation of T. gondii in red deer from two areas in Stelvio National park (Italian Central Alps), and three Generalized Linear Models were set up to evaluate: (1) the epidemiological factors influencing the probability to get infected; (2) if the infection is acquired before the breeding season or in early pregnancy and (i) could cause early abortion and drive hinds to lose reproduction, (ii) may influence hinds’ fertility through a delay in the physiological development of foetus. During two consecutive weeks between the end of November and the beginning of December 2012, 81 red deer sera were collected during the ...